The Auger Radioisotope Microscope: an instrument for characterization of Auger electron multiplicities and energy distributions - Patrick R Stollenwerk; Stephen H Southworth; Francesco Granato; Amy Renne; Brahim Mustapha; Kevin G Bailey; Peter Mueller; Jerry Nolen; Thomas P O’Connor; Junqi Xie; Linda Young; Matthew R Dietrich (New Journal of Physics, 2025)
We describe a new instrument, the Argonne Auger Radioisotope Microscope (ARM), capable of characterizing the Auger electron (AE) emission of radionuclides, including candidates relevant in nuclear medicine. Our approach relies on event-by-event ion–electron coincidence, time-of-flight, and spatial readout measurement to determine correlated electron multiplicity and energy distributions of Auger decays. We present a proof-of-principle measurement with the ARM using x-ray photoionization of stable krypton beyond the K -edge and identify a bifurcation in the electron multiplicity distribution depending on the emission of K-LX electrons. Extension of the ARM to the characterization of radioactive sources of AE emissions is enabled by the combination of two recent developments: (1) cryogenic buffer gas beam technology to introduce Auger emitters into the detection region with well-defined initial conditions, and (2) large-area micro-channel plate detectors with multi-hit detection capabilities to simultaneously detect multiple electrons emitted in a single decay.